Вы находитесь на странице: 1из 54

12/10/2013 1

Equivalence and
Compound Interest
Minggu 3
12/10/2013 2
Time Value of Money
The value of money today is worth more than
its value in the next several years. So, the
interest of money is needed to compensate
its value changed.

12/10/2013 3
Interest
(1)
Simple Interest
The total interest earned/charged is linearly proportional to
the initial amount of the loan (principle), the interest rate and
the number of inteest value.
The formula of simple interest for several periods (N) is :


F = Future value of money
P = Present value of money (principle loan)
N = Number of periods (e.g, years)
i = Interest rate


(1 . ) F P i N = +
12/10/2013 4
Interest
(2)
Compound Interest
The interest charge of any interest value is based on the
remaining principle amount plus any accumulated interest
charge up to the beginning of the period.
The formula of compound interest for several periods is :


F = Future value of money
P = Present value of money (principle loan)
N = Number of periods (e.g, years)
i = Interest rate
N
P ( 1 + i ) F =
12/10/2013 5
Equivalence
(1)

Economic equivalence is established, in
general, when we are indifferent between a
future payment, or series of future payments,
and a present sum of money.
Its can affect the difference in repayment plans
although the value of money actually similar. It
can be explained by this example :
12/10/2013 6
Equivalence
(2)
Example : Four plans for repayment of $5000
in five years at 8% interest :
- Plan 1 : At end of each year pay $1000
principle plus interest due.

(1) (2) (3) (4) (5) (6)
Year
Amount owed
at beginning of
year
Interest owed
for that year
Total owed at
end of year
Principle
payment
Total end of
year payment
[8% x (2)] [(2) + (3)}
1 5000 400 5400 1000 1400
2 4000 320 4320 1000 1320
3 3000 240 3240 1000 1240
4 2000 160 2160 1000 1160
5 1000 80 1080 1000 1080
Total 1200 5000 6200
12/10/2013 7
Equivalence
(3)
- Plan 2: Pay Interest due at end of each year
and principal at end of five years

(1) (2) (3) (4) (5) (6)
Year
Amount
owed at
beginning of
year
Interest
owed for
that year
Total owed
at end of
year
Principl
e
payment
Total end of
year
payment
[8% x (2)] [(2) + (3)}
1 5000 400 5400 0 400
2 5000 400 5400 0 400
3 5000 400 5400 0 400
4 5000 400 5400 0 400
5 5000 400 5400 5000 5400
Total 2000 5000 7000
12/10/2013 8
Equivalence
(4)
- Plan 3 : Pay in five equal end-of-year
payments.

(1) (2) (3) (4) (5) (6)
Year
Amount owed
at beginning
of year
Interest
owed for
that year
Total owed
at end of
year
Principl
e
payment
Total end of
year
payment

[8% x (2)] [(2) + (3)}

1 5000 400 5400 852 1252
2 4148 331 4479 921 1252
3 3227 258 3485 994 1252
4 2233 178 2411 1074 1252
5 1159 93 1252 1159 1252
Total 1260 5000 6260
12/10/2013 9
Equivalence
(5)
- Plan 4 : Pay interest and principal at the end
of periods.

(1) (2) (3) (4) (5) (6)
Year
Amount owed
at beginning
of year
Interest
owed for
that year
Total owed
at end of
year
Principl
e
payment
Total end of
year
payment

[8% x (2)] [(2) + (3)}

1 5000 400 5400 0 0
2 5400 432 5832 0 0
3 5832 467 6299 0 0
4 6299 504 6803 0 0
5 6803 544 7347 5000 7347
Total 2347 5000 7347
12/10/2013 10
Equivalence
(6)
ratio = total interest paid /total amount owed
at the beginning of year.
Plan
Total Interest
paid
Total amount
owed at the
beginning of year
ratio
1 $ 1200 $ 15000 0,08
2 2000 25000 0,08
3 1260 15767 0,08
4 2347 29334 0,08
From our calculations, we more easily see why the repayment
plans require the payment of different total sums of money,
yet are actually equivalent to each other.
12/10/2013 11
Compound Interest
To facilitate equivalence computations, a series of
interest formulas will be derived. To simplify the
presentation, well use the following notation :
i = Interest rate per interest period (%)
n = Number of interest periods
P = A present sum of money
F = A future sum of money
A = An end-of-period cash receipt or disbursement in a
uniform series
12/10/2013 12
Single Payment Formulas
(1)
Single payment formulas, consist of :
1. Future Equivalent Values







In other words a present sum P increase in n periods to
P(1+i)
n
Therefore have a relationship between a present sum P and
its equivalent future sum F
F = P (1+i)
n
Year
Amount at
beginning of
interest period +
Interest for
period =
Amount at end
of interest
period
1'st year P + iP = P (1+i)
2'nd year P(1+i) + iP(1+i) = P(1+i)
2

3'rd year P(1+i)
2
+ iP(1+i)
2
= P(1+i)
3

n'th year P(1+i)
n-1
+ iP(1+i)
n-1
= P(1+i)
n

12/10/2013 13
Single Payment Formulas
(2)
The single payment compoud amount formula function notation
is
F = P(F/P,i,n)
example :
If $500 were deposited in a bank savings account, how much
would be in the account 3 years hence if the bank paid 6%
interest compounded annualy?

F = 500 (F/P,6%,3)
= 500 (1,191)
= $ 595,5


P = 500
F = ?
n = 3
i = 0,06
1 2 3
12/10/2013 14
Single Payment Formulas
(3)
2. Present Equivalent Values
If we take F = P(1+i)n and solve for P



This is the single payment present worth formula.
The equation :

In our notation becomes
P = F(P/F,i,n)

( )
( )
1
1
1
n
n
P F F i
i

= = +
+
( )
1
n
P F i

= +
12/10/2013 15
Single Payment Formulas
(4)
example :
An investor (owner) has an option to purchase a tract of
land that will be worth $ 10.000 in six years. If the value
of the land increases at 8% each year, how much sould
the investor be willing to pay now for this property ?






P = 10.000 (P/F,8%,6)
= 10.000 (0,6302)
= $6.302


P = ?
F = 10.000
n = 6
i = 0,08
1 2 3 4 5 6
12/10/2013 16
Uniform Series Formula
(1)
According to the equation F=P(1+i)
n
, well use this relationship in
uniform series derivation

= + + +


In the general case for n years,
F = A(1+i)
n-1
+ . + A(1+i)
3
+ A(1+i)
2
+ A(1+i) + A

Multiplying equation above by (1+i),
(1+i)F = A(1+i)
n
+ . + A(1+i)
4
+ A(1+i)
3
+ A(1+i)
2
+ A(1+i)

A A A A
F =
A
A(1+i)
3
+
A
A(1+i)
2
+
A
A(1+i) +
A
A
12/10/2013 17
Factoring out A from two equation above and subtracting them,
(1+i)F = A[(1+i)
n
+ . + (1+i)
4
+ (1+i)
3
+ (1+i)
2
+ (1+i)]
F = A[(1+i)
n-1
+ . + (1+i)
3
+ (1+i)
2
+ (1+i) + 1]
iF = A[(1+i)
n
1]

Solving equation for F,

The term within the bracket


is called uniform series compound amount factor and the
notation is (F/A,i,n)
F = A (F/A,i,n)
(

+
=
i
i
A F
n
1 ) 1 (
(

+
i
i
n
1 ) 1 (
Uniform Series Formula
(2)
12/10/2013 18
Uniform Series Formula
(3)
If the equation is solved for A, we have



Where


is called the uniform series sinking fund factor and is written
as (A/F,i,n)
A = F (A/F,i,n)

(1 ) 1
n
i
A F
i
(
=
(
+

(1 ) 1
n
i
i
(
(
+

12/10/2013 19
Uniform Series Formula
(4)
We know that F = P (1+i)
n
, then



Solving equation for P,


Where


is called the uniform series present worth factor and is written
as (P/A,i,n)
P = A (P/A,i,n)

(1 ) 1
(1 )
n
n
i
P i A
i
(
+
+ =
(

(1 ) 1
(1 )
n
n
i
P A
i i
(
+
=
(
+

(1 ) 1
(1 )
n
n
i
i i
(
+
(
+

12/10/2013 20
Uniform Series Formula
(5)
If the equation is solved for A from P, we have



Where


is called the uniform series capital recovery factor and is
written as (A/P,i,n)
A = P (A/P,i,n)
(1 )
(1 ) 1
n
n
i i
A P
i
(
+
=
(
+

(1 )
(1 ) 1
n
n
i i
i
(
+
(
+

12/10/2013 21
Uniform Series Formula
(6)

Example 1 :
Using a 15% interest rate, compute the value
of F in the following cash flow :






Solution :we see that the cash flow diagram is not the
same as the sinking fund factor diagram
A =100
F = ?
0
year cash flow
1 +100
2 +100
3 +100
4 0
5 -F
12/10/2013 22
Uniform Series Formula
(7)


F
1
= 100(F/A,15%,3)
= 100(3,472)
= 347,2
F = F
1
(F/P,15%,2)
= 347,2(1,322)
= $ 459
A =100
F = ?
0
A =100
F = ?
0
F
1
P = F
1
F = ?
12/10/2013 23
Uniform Series Formula
(8)
Example 2 :
Using a 15% interest rate, compute the value of
P in the following cash flow

P = ?
20
20
30
0
year
cash
flow
0 -P
1 0
2 20
3 30
4 20
12/10/2013 24
Uniform Series Formula
(9)
Solution :




P=P
1
(P/F,15%,1) P
1
= A(P/A,15%,3) + F(P/F,15%,2)
P
1
= 20(P/A,15%,3) + 10(P/F,15%,2)
P
1
= 20(2.283) + 10(0.7561)
P
1
= 45.66 + 7.561 = 53.221
P = 53.221(0.8696)
P = 46.28
P
20 20
30
20 20
10
20
P
1
20
20
30
P
1
P
1
P
1
0 0
12/10/2013 25
Relationship Between
Compound Interest Factor
(1)

Single Payment
Compound amount factor = 1 / Present worth factor

Uniform Series
Capital recovery factor = 1 / Present worth factor

Compound amount factor = 1 / Sinking fund factor

) , , / (
1
) , , / (
n i F P
n i P F =
) , , / (
1
) , , / (
n i A P
n i P A =
) , , / (
1
) , , / (
n i F A
n i A F =
12/10/2013 26
Relationship Between Compound
Interest Factor
(2)
Uniform series present worth factor is simply the sum of the n
terms of the single payment present worth factor

Uniform series compound amount factor equals 1 plus the sum
of (n-1) terms of the single payment compound amount factor.

Uniform series capital recovery factor equals the uniform series
sinking fund factor puls i

=
=
n
J
J i F P n i A P
1
) , , / ( ) , , / (

=
+ =
1
1
) , , / ( 1 ) , , / (
n
J
J i P F n i A F
i n i F A n i P A + = ) , , / ( ) , , / (
12/10/2013 27
Arithmetic Gradient
(1)
Arithmetic Gradient is a series of increasing cash
flows.
Derivation of arithmetic gradient factor :



= + .. + +



F = G(1+i)
n-2
+ 2G(1+i)
n-3
+ + (n-2)G(1+i)
1
+ (n-1)G
or
F = G[(1+i)
n-2
+ 2(1+i)
n-3
+ + (n-2)(1+i)
1
+ (n-1)]
F
0
G
2G
(n-2)G
(n-1)G
F
I

G
F
II

(n-2)G
F
III

G
2G
(n-2)G
12/10/2013 28
Arithmetic Gradient
(2)
Multiply equation above by (1+i) and factor out G,
(1+i)F = G[(1+i)
n-1
+ 2(1+i)
n-2
+ + (n-2)(1+i)
2
+ (n-1)(1+i)]
Subtracting two equation above,
F + iF F = G[(1+i)
n-1
+ (1+i)
n-2
+ + (1+i)
2
+ (1+i) +1] nG
The term in the bracket were shown to equal the series compound
amount factor :

Thus the equation becomes

1 2 2 1
(1 ) 1
[(1 ) (1 ) ... (1 ) (1 ) 1]
n
n n
i
i i i i
i

+
+ + + + + + + + + =
(1 ) 1
n
i
iF G nG
i
(
+
=
(

12/10/2013 29
Arithmetic Gradient
(3)
Rearranging and Solving for F,


Using F = P (1+i)
n
,




The term in the bracket

is called arithmetic gradient present worth factor and denote by
(P/G,i,n)
(1 ) 1
n
G i
F n
i i
(
+
=
(

(1 ) 1 1
(1 )
n
n
G i
P n
i i i
( ( +
=
( (
+

2
(1 ) 1
(1 )
n
n
i in
G
i i
(
+
=
(
+

2
(1 ) 1
(1 )
n
n
i in
i i
(
+
(
+

12/10/2013 30
Arithmetic Gradient
(4)
Using then,







The term in the bracket


is called arithmetic gradient uniform series factor and denote
by (A/G,i,n)
(

+
=
i
i
A F
n
1 ) 1 (
(1 ) 1
(1 ) 1
n
n
G i i
A n
i i i
( ( +
=
( (
+

(

+
+
=
i i i
in i
G
n
n
) 1 (
1 ) 1 (
(

+
+
i i i
in i
n
n
) 1 (
1 ) 1 (
12/10/2013 31
Arithmetic Gradient
(5)
Example :
One a certain piece of machinery it is estimated that the
maintenance expense will be as follows :
what is the equivalent uniform annual maintenance cost for
the machinery if 6% interest is used




100
400
200
300
year
cash
flow
1 $ 100
2 200
2 300
4 400
A A A A
12/10/2013 32
Arithmetic Gradient
(6)



A = 100 + G (A/G,i,n)
= 100 + 100(A/G,6%,4)
= 100 + 100(1,427)
= $ 242,7

100
400
200
300
0
300
100
200
100
100 100 100
12/10/2013 33
Geometric Gradient
(1)
Year Cash Flow
1 100.00 = 100.00
2 100.00 + 10%(100.00) = 100(1 + 0.10)
1
= 110.00
3 110.00 + 10%(110.00) = 100(1 + 0.10)
2
= 121.00
4 121.00 + 10%(121.00) = 100(1 + 0.10)
3
= 133.10
5 133.10 + 10%(133.10) = 100(1 + 0.10)
4
= 146.41

12/10/2013 34
Geometric Gradient
(2)
100.00
110.00
121.00
133.10
146.41
12/10/2013 35
Geometric Gradient
(3)
From the table, we get : $100.00(1 + g)
n-1

General Form : A
n
= A
1
(1 + g)
n-1

where : g = Uniform rate of cash flow
A
1
= Value of A at Year 1
A
n
= Value of A at any Year n
Present worth P
n
of any cash flow A
n
:
P
n
= A
n
(1 + i)
-n
12/10/2013 36
Geometric Gradient
(4)
So, P
n
= A
1
(1 + g)
n-1
(1 + i)
-n
This may be rewritten as



Present worth of the entire gradient series of cash flow:


1
1
1
1
1
) 1 (

|
.
|

\
|
+
+
+ =
n
n
i
g
i A P

|
.
|

\
|
+
+
+ =
n
x
x
i
g
i A P
1
1
1
1
1
1
) 1 (
12/10/2013 37
Geometric Gradient
(5)
A
1
A
2
A
3
A
n-1
A
n
P
12/10/2013 38
Geometric Gradient
(6)
In general case where i g ;





Let a = A
1
(1 + i)
-1
and b = {(1+g) / (1+i)}
then the equation becomes :

2
1
1
1
1
1
1
1
1
) 1 (
1
1
) 1 ( ) 1 (
|
.
|

\
|
+
+
+ +
|
.
|

\
|
+
+
+ + + =

i
g
i A
i
g
i A i A P
1
1
1
1
1
) 1 ( ...

|
.
|

\
|
+
+
+ + +
n
i
g
i A
12/10/2013 39
Geometric Gradient
(7)
P = a + ab + ab
2
+ . + ab
n-1
multiply the equation above by b :
bP = ab + ab
2
+ ab
3
+ . + ab
n-1
+ ab
n

subtract two equation above :
P bP = a ab
n

P(1 b) = a(1 b
n
)

P = a(1 b
n
) / (1 b)
12/10/2013 40
Geometric Gradient
(8)
Replacing original value for a and b then :

|
|
|
|
|
.
|

\
|
|
.
|

\
|
+
+

|
.
|

\
|
+
+

+ =

i
g
i
g
i A P
n
1
1
1
1
1
1
) 1 (
1
1
|
|
.
|

\
|

+ +
=

g i
i g
A P
n n
) 1 ( ) 1 ( 1
1
where i g
12/10/2013 41
Geometric Gradient
(9)
Cash flow that applicable where the period-by-period change is
a uniform rate
Using the formula : :
Geometric series present worth factor where i = g,


Where i = g :

(

+ +
=

g i
i g
n i g A P
n n
) 1 ( ) 1 ( 1
) , , , / (
| |
1
) 1 ( ) , , , / (

+ = i n n i g A P
12/10/2013 42
Geometric Gradient
(10)
Example :
The first year mintenance cost for a new automobile is
estimated to be $100 , and it increases at a uniform rate of
10% per year. What is the present worth of cost of the first five
years of maintenance in this situation, using an 8% interest
rate?
Year maintenance cost PW
n (P/F,8%,n)
1 100 = 100 x 0,9259 $92,59
2 100 + 10%(100) = 110 x 0,8573 94,3
3 110 + 10%(110) = 121 x 0,7938 96,05
4 121 + 10%(121) = 133,1 x 0,735 97,83
5 133,1 + 10%(133,1)= 146,41 x 0,6806 99,65
$480,42
12/10/2013 43
Geometric Gradient
(11)
P = A1 1 (1 + g)
n
(1+i)
-n
i g
= 100 1 (1,1)
5
(1,08)
-5
= $480,42
0,02

12/10/2013 44
Nominal and Effective Interest
(1)
Nominal interest rate per year, r , is the annual interest
rate without considering the effect of any compounding
example : the bank pays 2.5 % interest every six
months. The nominal interest rate per year , r , therefor,
is 2 x 2.5 % = 5%
Effective interest rate per year, i
eff
, is the annual interest
rate taking into account the effect of any compounding
during the year.
Example : we saw $100 left in the savings account for
one year increased to $105.06, so the interest paid was
$5.06. the effective interest rate per year, i
eff
is
$5.06/$100 = 5.06%
12/10/2013 45
Nominal and Effective Interest
(2)

If : r = Nominal interest rate per year
i = effective interest rate per compounding
subperiod
m= Number of compounding subperiods per year.
i
eff
= (1 + r/m)
m
1 atau i
eff
= (1 + i)
m
1.

For continuous compounding, maka i
eff
= e
r
- 1

12/10/2013 46
Nominal and Effective Interest
(3)

If a savings bank pays 1.5% interest every three
months, what are the nominal and effective interest rate
per year ?
r = 4 x 1,5% = 6 %
i
eff
= (1+r/m)
m
1 atau i
eff
= (1+i)
m
1
= (1+0,06/4)
4
1 = (1+0,015)
4
- 1
= 0,061 = 0,061
= 6,1 % = 6,1 %

12/10/2013 47
Continuous Compounding
(1)
Since The interest period is normally one year, well use
the following notation :
- r = Nominal interest rate per year
- m = Number of compounding subperiods per year
- r/m = Interest rate per interest period
- mn = Number of interest periods in n years

F = P(1+i)
n
may be rewritten as F = P(1+r/m)
mn
if we increase m without limit, m becomes very large
approaches infinity, and r/m becomes very small
approaches zero
12/10/2013 48
Single Payment Interest Factors
Continuous Compounding
(1)
lim 1
mn
x
r
F P
m

| |
= +
|
\ .
( )
1/
lim 1
rn
x
x
F P x

(
= +

If we set x = r/m, then mn may be written as (1/x)(rn)



Because


F = P(1+i)
n
becomes F = Pe
rn
= P(F/P,r,n) and
P = F(1+i)
-n
becomes P = Pe
-rn
= F(P/F,r,n)



( )
1/
lim 1 2.71828
x
x
x e

+ = =
12/10/2013 49
Single Payment Interest Factors
Continuous Compounding
(2)
Example :
If you were to deposit $2000 in a bank that pays
5% nominal interest, compounded continuously,
how much would be in the account at the end of
two years?
r = 0,05 ; n = 2
F = P(e
r n
)
F = 2000(e
0,05x2
)
= $ 2210,4
12/10/2013 50
Uniform Payment Series
Continuous Compounding
If we subsitute the equation i = e
r
1 into the equations
for periodic compounding, we get :
a. Continuous Compounding Sinking Fund :
(A/F,r,n) = e
r
1
e
r n
1
b. Continuous Compounding Capital Recovery :
(A/P,r,n) = e
r n
(e
r
1)
e
r n
1
c. Continuous Compounding Series Compound
Amount
(F/A,r,n) = e
r n
1
e
r
1

12/10/2013 51
Uniform Payment Series
Continuous Compounding(2)
A man deposited $500 per year into a credit union that
paid 5% interest, compounded annualy. At the end of
five years, he had $2763 in the credit union. How much
would he have if the paid 5% nominal interest,
compounded continuously ?
A = $500 ; r = 0,05 ; n = 5
F = A(F/A,r,n) = e
r n
1
e
r
1
= 500 e
0,05(5)
1
e
0,05
1
= $ 2769,84


12/10/2013 52
Continuous, Uniform Cash Flow (1
period) with continuous compounding at
nominal interest rate (r)
(1)
Uniform cash flow P be distributed over m subperiods within
one period (n = 1)
Compound Amount :



Present Worth :

1 2 3 n
F
1 2 3 n
P
(


=
r
rn r
re
e e
n r P F
) )( 1 (
) , , / (
(


=
rn
r
re
e
n r F P
) 1 (
) , , / (
P
F
12/10/2013 53
Continuous, Uniform Cash Flow (1
period) with continuous compounding at
nominal interest rate (r)
(2)
Example :
A self-service gasoline station has been equipped with an
automatic teller machine (ATM). Customer may obtains
gasoline simply by inserting their ATM bank card into the
machine and filling their car with gasoline, the ATM unit
automatically deducts the gasoline purchase from the
customers bank account and credits it to the gas stations
bank account. The gas station received $40.000 / month in
this manner with the cash flowing uniformly troughout the
month. If the bank pays 9% nominal interest, compounded
continuously, how much will be in the gasoline station bank
account at the end of the month?

12/10/2013 54
Continuous, Uniform Cash Flow (1
period) with continuous compounding at
nominal interest rate (r)
(3)
r = nominal interest rate per month
= 0,09 / 12 = 0,0075

F = P (e
r
1)(e
r n
) = 40.000 (e
0,0075
1)(e
0,0075(1)
)
re
r
0,0075e
0,0075


F = $40150,4